2021
DOI: 10.1002/aoc.6383
|View full text |Cite
|
Sign up to set email alerts
|

Amine‐functionalized nano‐NaY zeolite for the synthesis of N‐acetyl pyrazoles and dihydropyrimidines

Abstract: An efficient base‐catalyzed synthesis of dihydropyrimidines and N‐acetyl pyrazoles is reported using 1‐(2‐aminoethyl)piperazine‐modified nano‐NaY zeolite (ZeSi–AP) under mild and green conditions. The structure of the catalyst was identified by using FT‐IR, XRD, TGA, DTA, DLS, SEM, TEM, and elemental analyses. This heterogeneous catalyst has many benefits, such as a simple work‐up procedure, high product yield, and it is easily regenerated and reused at least for four cycles without losing its activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 67 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…We present the results in Figures 3 and 4. We present the TGA/DTA curves of the natural and modified zeolite to show the stages of composition in Figure 3 [42,43]. After the modification, the increase in the Si/Al ratio (by 0.6) and silicon content (by 7.3%) indicated that we could graft the groups of APTES onto the natural zeolite.…”
Section: Characteristics Of Natural and Modified Zeolitementioning
confidence: 99%
See 1 more Smart Citation
“…We present the results in Figures 3 and 4. We present the TGA/DTA curves of the natural and modified zeolite to show the stages of composition in Figure 3 [42,43]. After the modification, the increase in the Si/Al ratio (by 0.6) and silicon content (by 7.3%) indicated that we could graft the groups of APTES onto the natural zeolite.…”
Section: Characteristics Of Natural and Modified Zeolitementioning
confidence: 99%
“…We present the results in Figures 3 and 4. We present the TGA/DTA curves of the natural and modified zeolite to show the stages of composition in Figure 3 [42,43]. According to the TGA curve in Figure 3a, natural zeolite has two stages of composition.…”
Section: Naturalmentioning
confidence: 99%